Efficiency of Cryogenic Rehabilitation of Antiterrorist Operation Combatants by Means of Whole-Body Air Cryotherapy - Nahlov, Ðžlexandr V.; Tovstukha, Ihor A. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 180